Antibacterial activity of Malaysian mango kernel - Al-Shwyeh, Hussah Abdullah; Mirghani, Mohamed Elwathig Saeed; Jamal, Parveen (Academic Journals, 2011)
Mango (Mangifera indica) is a fruit belonging to the genus Mangifera and family Anacardiaceae, consisting of numerous species of tropical fruiting trees in the flowering plant. Mango has been reported to have high antibacterial activity against Gram positive bacteria, aids the development of the placenta and fetus, and helps in the metabolic activities of teeth, the retina and skin, while preventing anemia. In addition, it also helps to tighten the capillary vessels. However, the significant increase in mango consumption in domestic activity leads to the accumulation of waste, especially its kernel. This study attempts to screen three varieties of mango kernels: waterlily, lemak and shakran extracted using four different extraction solvent: ethanol, methanol, acetone and distilled water to examine the potential of mango kernel as natural antibacterial against four bacterial strains: Staphylococcus aureus, Bacillus subtillis, Escherichia coli and Pseudomonas aeruginosa. Disc diffusion assay was employed to determine the antibacterial activity. Optimization of process conditions for extraction of antibacterial activity (having widest inhibition zone) was conducted in shake flasks based on the experimental design suggested by central composite design (CCD) from Design Expert v.6.0.8. by manipulating reaction temperature (°C), reaction time (hour) and agitation speed (rpm). It was found that waterlily had the best antibacterial activity, utilizing ethanol as the extraction solvent. Optimization of this sample was run and the maximum antibacterial activity (16.80 mm) was reached at 37°C, 24 h and 200 rpm. Identification of the active compound using gas chromatography-mass spectrometry (GC-MS) recognized phenol, 2,4-bis (1,1-dimethylethyl) as the possible compound responsible for antibacterial activity. This finding would probably become an alternative source of new and natural antibacterial agents.